Flame-made Cu/ZrO2 catalysts with metastable phase and strengthened interactions for CO2 hydrogenation to methanol. Issue 61 (12th July 2021) - Yang, Meng; Yu, Jiafeng; Tong, Xin; Sun, Xingtao; Xu, Hengyong; Sun, Jian
Abstract : The strengthened Cu–Zr interactions in FSP-Cu/ZrO2 were beneficial for the adsorption of bi-HCOO* and the generation of methoxy species (*OCH3 ) at the interface by enhancing Cu + species and Ov compared to the one made by the traditional method. Abstract : Facile synthesis of a highly efficient Cu/ZrO2 catalyst by a flame spray pyrolysis (FSP) method was developed for methanol production from CO2 hydrogenation. The instantaneous quenching process from extremely high temperature in FSP was used for rational design of a Cu/ZrO2 catalyst, not only producing the metastable tetragonal phase ZrO2, but also strengthening the metal–support interaction. The methanol yield of one-step synthesized FSP-Cu/ZrO2 was 3 times higher than the one made by the traditional method. This strategy is anticipated to pave the way for strengthening metal–support interactions of supported catalysts.